2019
DOI: 10.1101/674424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oligomeric state of the ZIKV E protein defines protective immune responses

Abstract: 8The current leading Zika vaccine candidates in clinical testing are based on live or killed virus 9 platforms, which have safety issues, especially in pregnant women. Zika subunit vaccines, 10 however, have shown poor performance in preclinical studies. We hypothesized that Zika 11Envelope (E) protein subunit vaccines have performed poorly because the antigens tested have 12been recombinant E monomers that do not display critical quaternary structure epitopes present 13on Zika E protein homodimers that cover … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Recently, a characterization of two dimeric E antigens was published, dimerization was achieved by the A264C mutation or replacing the E transmembrane domain with the FC fragment of a human IgG (39). While this manuscript was under preparation, two other articles reported development and evaluation of dimer-based subunit vaccines similar to that described in here (40,41). The authors showed that in all three cases the antigens were able to induce in mice the production of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a characterization of two dimeric E antigens was published, dimerization was achieved by the A264C mutation or replacing the E transmembrane domain with the FC fragment of a human IgG (39). While this manuscript was under preparation, two other articles reported development and evaluation of dimer-based subunit vaccines similar to that described in here (40,41). The authors showed that in all three cases the antigens were able to induce in mice the production of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In solution at 37°C, the ZVrecE glycoprotein is in an equilibrium that greatly favors monomers over homodimers (9). We compared the binding of several ZIKV-specific human mAbs, including B11F to ZVrecE monomers and stable homodimers (stabilized by the introduction of an intermolecular disulfide bond (18). Control antibodies that preferentially bound monomers (pan-flaviviral fusion-loop targeting mAb 1M7) or homodimers (quaternary epitope-specific mAb EDE C10) confirmed the oligomeric state of our antigens ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Structural analysis of DH1017.Fab in complex with whole ZIKV virion identified a quaternary epitope footprint encompassing primarily DII that differs from that of known potently ZIKV-neutralizing mAbs. Antibody responses targeting quaternary epitopes on multimeric E protein epitopes or mature virions are associated with protection from ZIKV infection in mice (Maciejewski et al, 2020; Metz et al, 2019). Recognition of a quaternary epitope on ZIKV is the defining feature of a class of potently neutralizing mAbs (Collins et al, 2019; Hasan et al, 2017b; Long et al, 2019; Rogers et al, 2017; Sapparapu et al, 2016; Stettler et al, 2016).…”
Section: Discussionmentioning
confidence: 99%